World Bank Pharmaceuticals - Govindaraj, Ramesh; Reich, Michael R.; Cohen, Jillian C. (World Bank, Washington, DC, 2013)
Pharmaceuticals have a major impact on health, on government and household spending, and on health systems. Despite the fundamental role of pharmaceuticals, there remains a profound gap between the benefit which pharmaceuticals have to offer and the reality that for millions of people -- particularly poor and disadvantaged people -- medicines are unavailable, unaffordable, unsafe or improperly used. This World Bank Pharmaceuticals Discussion Paper provides a pragmatic analysis of some of the causes for this gap and strategic directions to help close this gap. The strategic directions outlined in this Pharmaceuticals Discussion Paper complement and reinforce the objectives outlined in the WHO Medicines Strategy: 2000-2003 (World Health Organization, Geneva, 2000, WHO/EDM/2000.1). The WHO strategy describes specific objectives, expected outcomes, and progress indicators in the areas of drug policy, access to essential drugs, quality and safety, and rational use of medicines. Both the World Bank and the WHO initiatives rest on a fundamental commitment to work with governments, on governmental organizations, the private sector, professional bodies, and other key actors to help strengthen the pharmaceutical sector and its ability to contribute to improved health outcomes.. The current burden of disease falling on the two billion people living on less than one dollar per day undermines both individual well-being and collective economic development. Much of this burden of disease can be reduced by securing the availability, affordability, and rational use of essential drugs of assured quality. Yet this aim can not be achieved by governments alone, by individual multilateral organizations working alone, or by any other individual organization. It can only be achieved when committed governments and local organizations are supported by clear, consistency, and mutually compatible approaches by agencies such as the World Bank, WHO, UNICEF, others in the UN family, bilateral donors, and the broader development community. This discussion paper provides an important contribution to this process.